The Insensitivity of the Union Movement to the Real Needs of the Union Members - Humphries, Michael (Relations industrielles / Industrial Relations, 1968)
After a brief review of Maslow's and Herzsberg's theories, the author proposes three solutions to help unions in satisfying the real needs of its members.